Winged lions, Port Trust War Memorial - Ghosh, Ayan (2023)
Winged lions on the Port Trust War Memorial. The motif is an ancient one, having origins in Mesopotamia and Assyria. It appeared on the flag of the Republic of Venice, a major maritime power during the Middle Ages. The winged lion motif appears in many buildings in Mumbai which were designed by architects inspired by Venetian Gothic architecture.